Peran Attachment dan Dukungan Keluarga dalam Perkembangan Emosi dan Prestasi Santri Ma’had Insan Cendikia MTs Negeri 1 Banyumas - Hasri Nur Azizah; Septi Gumiandari; Ade Hidayat (Universitas Muhammadiyah Metro, 2026)
Adolescence is a critical period characterized by emotional turmoil and self-discovery. The separation of adolescents from family to live in the dormitory poses mixed pressures of academic and psychological adaptation. In Ma'had Insan Cendikia MTs Negeri 1 Banyumas, Tahfidzul Qur'an students showed significant differences in the achievement and consistency of memorization. Some students experience prolonged homeicks that degrade performance, while others are able to adapt quickly and achieve stable. This phenomenon indicates the role of psychological factors, in particular the pattern of attachment to parents and family support.This study aims to: (1) describe the pattern of attachment between students with parents and caregivers in the dormitory environment, (2) understanding the meaning and form of family support received by students during living in the dormitory, and (3) analyze the dynamics of the development of santri emotions as well as their relationship with academic achievement. The data is collected through in-depth interviews with nine key informants consisting of students, dormitory guides, and parents, and equipped with participatory observation and documentation analysis. The results showed that: (1) there are two patterns of attachment, namely the attachment of safety in santri who are able to choose the source of support adaptively and attachment to santri with high dependence on parents accompanied by emotional turmoil; (2) family support manifested in four forms, namely emotional support, material, informational, and appreciation of the achievement of memorization; and (3) the dynamics of santri emotional development progressed through three phases, namely the homesick phase, stabilization phase, and the phase of self-formation.